Re-evaluation of Adrenocorticotropic Hormone and Melanocyte Stimulating Hormone Activation of GPR139 in Vitro - Nepomuceno, Diane; Kuei, Chester; Dvorak, Curt; Lovenberg, Timothy; Liu, Changlu; Bonaventure, Pascal (Frontiers in Pharmacology, 2018)
It is now well established that GPR139, a G-protein coupled receptor exclusively expressed in the brain and pituitary, is activated by the essential amino acids L-tryptophan (L-Trp) and L-phenylalanine (L-Phe) via Gq- coupling. The in vitro affinity and potency values of L-Trp and L-Phe are within the physiological concentration ranges of L-Trp and L-Phe. A recent paper suggests that adrenocorticotropic hormone (ACTH), alpha and beta melanocyte stimulating hormones (a-MSH and b-MSH) and derivatives can also activate GPR139 in vitro. We tested this hypothesis using guanosine 5’-o-(3-[35S]thio)-triphosphate binding (GTPgS), calcium mobilization and [3H]JNJ-63533054 radioligand binding assays. In the GTPgS binding assay, a-MSH,a-MSH1-9/a-MSH1-10 and b-MSH had no effect on [35S]GTPgS incorporation in cell membranes expressing GPR139 up to 30 uM in contrast to the concentration dependent activation produced by L-Trp, JNJ-63533054 and TC-09311. ACTH slightly decreased the basal level of [35S]GTPgS incorporation at 30 uM. In the GPR139 radioligand binding assay, a moderate displacement of [3H]JNJ-63533054 binding by ACTH and b-MSH was observed at 30 uM (40 and 30%, respectively); a-MSH, a-MSH1-9/a-MSH1-10 did not displace any specific binding at 30 uM. In three different host cell lines stably expressing GPR139, a-MSH and b-MSH did not stimulate calcium mobilization in contrast to L-Trp, JNJ-63533054 and TC-09311. ACTH, a-MSH1-9/a-MSH1-10 only weakly stimulated calcium mobilization at 30 uM (< 50 % of EC100). We then co-transfected GPR139 with the three melanocortin (MC) receptors (MC3R, MC4R and MC5R) to test the hypothesis that ACTH, a-MSH and b-MSH might stimulate calcium mobilization through a MCR/GPR139 interaction. All three MC peptides stimulated calcium response in cells co-transfected with GPR139 and MC3R, MC4R or MC5R. The MC peptides did not stimulate calcium response in cells expressing MC3R or MC5R alone consistent with the Gs signaling transduction pathway of these receptors. In agreement with the previously reported multiple signaling pathways of MC4R, including Gq transduction pathway, the MC peptides produced a calcium response in cells expressing MC4R alone. Together, our findings do not support that GPR139 is activated by ACTH, a-MSH and b-MSH at physiologically relevant concentration but we did unravel an in vitro interaction between GPR139 and the MCRs